Relationship between human genital epithelial cells, squamous metaplasia and HPV16-mediated oncogenesis - Sun, Qi, 1960- (1996)
Thesis (Ph.D.)--Memorial University of Newfoundland, 1996. Medicine Bibliography: leaves 346-398 The stratified squamous epithelium (SSE; for abbreviations, see lists on page xviii) in the transformation zone (TZ) of human uterine cervix is metaplastic in nature, and the TZ is the most common site for carcinomas related to infection by human papillomavirus type 16 (HPV 16). This study attempted to elucidate the mechanisms for the high incidence of HPV16-mediated malignancy inthemetaplastic SSE. -- In vitro cultured normal human keratinocytes (HKC) from foreskin (HFK) and ectocervix (HEC), and epithelial cells from human endocervix (HEN) were reconstructed into epithelia using an //; vivo nude mice model. While HKC from both HFK and HEC formed well-differentiated SSE, HEN formed an epithelium displaying morphological features of immature metaplastic SSE, which was substantiated by the expression patterns of cytokeratins (CKs). These results established the endocervical origin of metaplastic SSE in the TZ. -- HEN immortalized by HPV 16 genomic DNA (HEN 16) formed highly dysplastic lesions, whereas lesions formed by the immortalized HKC (HKC 16) displayed low grade dysplastic changes in the same in vivo system. The CK expression patterns in lesions from both types of cells supported the pathological features. Northern and Southern blot analyses for the immortalized cells cultured in vitro failed to reveal any significant differences between the HPV16-immorta!ized cells in the viral DNA status, the expression of the viral E7 and E5 oncogenes, and the expression of the cellular protooncogenes c-myc and H-ras. Therefore, E7 expression in the in vivo implants from the immortalized cells was examined. In situ hybridization assays showed that, while E7 expression was limited to the basal cells of the HKC 16 lesions, E7 was expressed throughout the HEN 16 lesion. The compartmentalized E7 expression in the HKC 16 lesions was not due to a defunct transcription mechanism, since the cells that did not express E7 did transcribe CK1. These results suggested that HKC, but not HEN, possess a cell type-specific mechanism to repress HPV16 oncogene expression, and this mechanism is functional only upon undergoing programmed squamous differentiation. -- In the in vivo system, there may have been uncontrollable variables, such as cytokines induced by surgical trauma or by immune responses to the lesions. To exclude a possible involvement of such factors in the putative repression function for HPV E7, the immortalized cells were tested in the organotypic (raft) culture system. Raft culture is an in vitro epithelia reconstruction system, which allows control over the epithelial reconstruction conditions. The morphology and E7 expression of the raft lesions were similar to those in the in vivo implants, indicating that this HPV repression function is independent of in vivo factors. -- The epithelial-specific expression of HPV16 genes, including that of the E7 gene, is controlled by the long control region (LCR) in the HPV16 genome. Thus, the role of the HPVI6 LCR in the compartmentalized expression of E7 was evaluated. Immortalized cell lines were established by in vitro transfection of the pSV21667 plasmid, which contained the HPV16 E6 and E7 genes regulated by the SV40 early promoter. The immortalized cells all contained integrated viral oncogenes and expressed E7 at a comparable level in in vitro monolayer cultures. Furthermore, the viral oncogenes appeared to retain the functional heterologous control elements, since transforming growth factor p (TGF-P) repressed E7 expression in the cells immortalized by HPV 16 genomic DNA, but not in those immortalized by pSV21667. The signal transduction pathway for TGF-P was functional in all the cell lines, because c-myc expression showed normal response to TGF-p. Unexpectedly, the raft lesions from the pSV21667-immortalized HEN and HKCs showed pathological features, E7 expression patterns, and 5-AZ responses very similar to those of their respective HPV16 genomic DNA-immortalized counterparts. These results indicated that the squamous differentiation-associated cellular mechanism responsible for the compartmentalized E7 expression in the HKC lesions is not dependent on the HPV16 LCR. -- 5-azacytidine (5-AZ), a DNA demethylation agent, decompartmentalized E7 expression in the raft of the immortalized HFK, which was accompanied with increased severity of dysplastic changes. Treatment of normal HEC with 5-AZ induced selective changes in the patterns of CK expression. Therefore, the compartmentalized E7 expression in the HKC lesions may result from a cellular mechanism that is functional for gene repression at a global level in differentiating HKC and is mediated by DNA methylation. -- To test the clinical relevance of the above observations, expression of the HPV16 E7 oncogene was examined by in situ hybridization in natural premalignant lesions occurring at the cervical metaplastic SSE (CINs) and vulval native SSE (VINs). The status of HPV16 DNA and permissiveness for viral vegetative replication in the lesions were evaluated by assessing viral DNA amplification and transcription of the viral LI structural gene with DNA and RNA in situ hybridization assays, respectively. In the VINs, E7 was expressed in the bottom layers of lesions, with viral DNA amplification and late gene expression in the differentiated upper layers. In contrast, E7 was expressed in the CINs throughout the lesions. Furthermore, in the immature metaplastic SSE, viral DNA replication occurred in the bottom cells, without the expression of the viral LI gene, in contrast to the upper layer viral DNA amplification in the mature metaplastic SSE. Thus, HPV16 infection in immature metaplastic SSE may represent a form of non-vegetative infection, and the expression of the HPV16 oncogenes and possibly the amplification of viral DNA were dysregulated. -- In summary, my studies constitute the first systematic and experimental dissection of the relationship between squamous metaplasia, cervical cancer and HPV 16 infection. The results showed that metaplastic SSE derives from HEN, that viral oncogene expression in HEN and HKC in conditions allowing squamous differentiation is distinct, and that this difference is specific for the cell types but not for the HPV16 LCR. The results from clinical samples revealed that HPV16 infection may undergo a distinct life cycle in the cervical immature metaplastic SSE, which is featured by persistent viral oncogene expression and dysregulated viral DNA amplification. Because persistent expression of the HPV16 oncogenes and viral DNA integration are common features of HPV16-containing cervical cancers, this state of non-vegetative infection may be important for the unusual susceptibility of the cervical metaplastic epithelium to HPV16-mediated oncogenesis.